Polysomnography for the management of oxygen supplementation therapy in infants with chronic lung disease of prematurity. (2nd November 2019) - Kulkarni, Gaurav; de Waal, Koert; Grahame, Sally; Collison, Adam; Roddick, Laurence; Hilton, Jodi; Gulliver, Tanya; Whitehead, Bruce; Mattes, Joerg
Abstract: Aim: Some infants with bronchopulmonary dysplasia (BPD) may require oxygen supplementation at home but a role for overnight polysomnography (PSG) in the management of home oxygen therapy has been rarely described. Methods: Forty-one infants with BPD born at less than 30 weeks gestational age were discharged with continuous home oxygen supplementation therapy between 2010 and 2013. PSG data were recorded on oxygen supplementation versus room air at median corrected age of 2 months (range 1–5 months) (first PSG after discharge to home). Those infants who continued oxygen supplementation therapy at home had at least one more PSG before oxygen therapy was discontinued (last PSG). We also collected PSG data in 10 healthy term infants (median age 3.5 months; range 2–4 months). Results: In infants with BPD in room air, increased numbers of central apneas, hypopneas, and SaO2 desaturations were the predominant PSG features with a median apnea–hypopnea index (AHI) of 16.8 events per hour (range 0–155). On oxygen supplementation therapy, median AHI dramatically improved (2.2, range 0–22; p < .001) and was not different from control infants (2.0, range 0–3.9; p = .31). AHI on room air at the last PSG when home oxygen was ceased was 4.1 per hour (range 0–13.8) slightly higher than in healthy infants. Conclusion: Central sleep disordered breathing in infants with BPD dramatically normalizes with low flow nasal cannula home oxygen therapy and improves with age. Mild central sleep disordered breathing remains detectable, although much improved, when compared with healthy infants at the time when the decision to cease home oxygen therapy was made by the physician.